Total Phenolic and Total Flavonoid Content, Individual Phenolic Compounds and Antioxidant Activity in Sweet Rowanberry Cultivars - Jana Orsavová; Tunde Juríková; Růžena Bednaříková; Jiří Mlček (MDPI AG, 2023)
Sweet rowanberry and its cultivars represent a less-known fruit species with significant antioxidant activity, mostly promoted by polyphenolic compounds. This paper examined seven Sorbus cultivars and evaluated their total polyphenolic and flavonoid content, as well as the content of individual polyphenolic compounds from the group of phenolic acids and flavonoids. It also determined their antioxidant activity using DPPH, ACW and ACL. Furthermore, to reflect the distribution of the contribution to antioxidant activity, correlations between antioxidant activity and the contents of ascorbic acid, vitamin E and individual phenolic compounds were established. The highest total phenolic content of 8307.4 mg kg−1 was determined in 'Granatina', with the main contribution of phenolic acid content of 7001.7 mg kg−1 and a significantly lower total flavonoid content of 1304.6 mg kg−1. Flavanols represented the most abundant group of flavonoids, with catechin being the second most frequent flavanol with the highest content of 633.67 mg kg−1 in 'Granatina'. Flavonols were represented by rutin and quercetin. 'Businka' displayed a significant vitamin E content of 4.77 mg kg−1, and 'Alaja Krupnaja' had the highest vitamin C level of 7.89 g kg−1. These results emphasize their potential health and nutritional benefits and, thus, their promising and valuable role in the food processing industry.